2019
DOI: 10.1007/s11947-019-02313-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Processing Alone or in Combination with Other Chemical or Physical Treatments as a Safety and Quality Preservation Strategy of Fresh and Processed Fruits and Vegetables: A Review

Abstract: Ultrasound (US) processing has emerged as a novel food preservation technology. This strategy has proved antimicrobial effects due to cavitation, which is the formation, growth, and collapse of bubbles that generate a localized mechanical and chemical energy. This technology can be applied by water so introducing it in the washing step to obtain safe fresh or fresh-cut products could be promising. The current review provides an overview of the current knowledge and recent findings on the use of US, alone or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 118 publications
0
28
0
3
Order By: Relevance
“…These enzymes are responsible for the color variations in frozen and raw vegetables and also, browning reactions. Sonication also imparts an antimicrobial effect which could be due to free radical formation and cavitation [119] . Mizrach et al [120] , gave a detailed description of the different changes, both physicochemical and physiological involved in maturation and growth, harvesting, and storage period (shelf life).…”
Section: Application Of Ultrasound In Food Industrymentioning
confidence: 99%
“…These enzymes are responsible for the color variations in frozen and raw vegetables and also, browning reactions. Sonication also imparts an antimicrobial effect which could be due to free radical formation and cavitation [119] . Mizrach et al [120] , gave a detailed description of the different changes, both physicochemical and physiological involved in maturation and growth, harvesting, and storage period (shelf life).…”
Section: Application Of Ultrasound In Food Industrymentioning
confidence: 99%
“…The combination of ultrasound and biocide (chlorine) has been of considerable interest since the 1990′s when the work in Mason’s group was first published [7] . In recent years, some studies have also highlighted the combination of ultrasound with other preservation technologies or compounds with inherent biocidal action aiming at exhibiting an inactivating synergistic effect [8] , [9] . Previous studies conducted in our lab also demonstrated an extraordinary synergistic effect of ultrasound and thyme essential oil nanoemulsion (TEON) against E. coil O157:H7.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed reviews on low-power ultrasound in food applications are found elsewhere [8] , [9] , [11] , [12] . The high-power ultrasound (>5 W/cm 2 ) at a lower frequency (around 40 kHz) [13] have been utilized in modifying food physicochemical properties and structures affording beneficial effects on the preservation [14] , [15] , maintaining quality [16] , [17] , and ensuring the safety of food products [18] . Moreover, the latter type of ultrasound was utilized in the functionalizing properties of rice starch and rice grain.…”
Section: Introductionmentioning
confidence: 99%